2023
DOI: 10.1039/d2qo01717b
|View full text |Cite
|
Sign up to set email alerts
|

In situ generated aminodiborane as a reagent for deoxygenative reduction of carboxamides to amines

Abstract: Herein, we report a new method for the synthesis of aminodiborane (µ-NH2B2H5), by the reaction of NH3BH3 and elemental iodine (I2). The in situ generated aminodiborane is used as a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…A great deal of work has been performed exploring BH 3 −NH 3 as a hydrogen source, 18,19 but it is also gaining prominence as a useful reducing agent. 20,21 Using appropriate catalysts and activators, it has been applied for the reduction of carbonyls, 22,23 esters, 24,25 amides, 26,27 and a variety of other functional groups. 28,29 As part of our program on borane−amines for organic synthesis, we recently reported efficient room temperature (RT) reductions of ketones 30 and carboxylic acids 31 to alcohols with BH 3 −NH 3 using catalytic (10 mol %) TiCl 4 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A great deal of work has been performed exploring BH 3 −NH 3 as a hydrogen source, 18,19 but it is also gaining prominence as a useful reducing agent. 20,21 Using appropriate catalysts and activators, it has been applied for the reduction of carbonyls, 22,23 esters, 24,25 amides, 26,27 and a variety of other functional groups. 28,29 As part of our program on borane−amines for organic synthesis, we recently reported efficient room temperature (RT) reductions of ketones 30 and carboxylic acids 31 to alcohols with BH 3 −NH 3 using catalytic (10 mol %) TiCl 4 .…”
mentioning
confidence: 99%
“…Borane–ammonia (BH 3 –NH 3 , 1a ) is an easily prepared, air and moisture stable alternative to borane–tetrahydrofuran (BTHF) and borane–dimethyl sulfide (BMS). A great deal of work has been performed exploring BH 3 –NH 3 as a hydrogen source, , but it is also gaining prominence as a useful reducing agent. , Using appropriate catalysts and activators, it has been applied for the reduction of carbonyls, , esters, , amides, , and a variety of other functional groups. , As part of our program on borane–amines for organic synthesis, we recently reported efficient room temperature (RT) reductions of ketones and carboxylic acids to alcohols with BH 3 –NH 3 using catalytic (10 mol %) TiCl 4 . During these projects, ketones or acids were selectively reduced in the presence of esters, which is not surprising given the fact that esters are poor substrates for reduction with BTHF or BMS .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Among the various B-N dehydrogenated species, 8 aminodiborane (m-NH 2 B 2 H 5 , ADB) has received recent interest in organic and inorganic syntheses. [9][10][11][12][13][14] ADB is a strained molecule, which is sensitive to moisture and air. The isolation of pure ADB as a reagent is cumbersome due to the high reactivity of the compound.…”
mentioning
confidence: 99%
“…11,12 So, in situ generation of ADB has been found to be a better alternative for the reduction reactions of various organic functional groups. [12][13][14] The in situ generated ADB has been reported for reduction of carboxylic acids to alcohols 12 and nitriles to amines. 13 Very recently, our group reported that by combining iodine and AB, ADB can be in situ generated which can be used to reduce amides to amines (Scheme 1).…”
mentioning
confidence: 99%